Influence of Surface Treatment on the Shear Bond Strength of Ceramics Fused to Cobalt-Chromium - Lombardo, Geraldo H. L.; Nishioka, Renato S. [UNESP]; Souza, Rodrigo O. A.; Michida, Silvia M. A. [UNESP]; Kojima, Alberto N.; Mesquita, Alfredo M. M.; Buso, Leonardo (Wiley-Blackwell, 2010)
Purpose: To evaluate the influence of surface treatment on the shear bond strength between a Co-Cr alloy and two ceramics.Materials and Methods: Forty-eight metal cylinders were made (thickness: 4 mm, height: 3.7 mm) according ISO TR 11405. The 48 metallic cylinders were divided into four groups (n = 12), according to the veneering ceramic (StarLight Ceram and Duceram Kiss) and surface treatments: air-particle abrasion with Al(2)O(3) or tungsten drill (W). Gr1: StarLight + Al(2)O(3); Gr2: StarLight + W; Gr3: Duceram + Al(2)O(3); and Gr4: Duceram + W. The specimens were aged using thermal cycling (3000 x, 5 to 55 degrees C, dwell time: 30 seconds, transfer time: 2 seconds). The shear test was performed with a universal testing machine, using a load cell of 100 kg (speed: 0.5 mm/min) and a specific device. The bond strength data were analyzed using ANOVA and Tukey's test (5%), and the failure modes were analyzed using an optical microscope (30x).Results: The means and standard deviations of the shear bond strengths were (MPa): G1 (57.97 +/- 11.34); G2 (40.62 +/- 12.96); G3 (47.09 +/- 13.19); and G4 (36.80 +/- 8.86). Ceramic (p = 0.03252) and surface treatment (p = 0.0002) significantly affected the mean bond strength values.Conclusions: Air-particle abrasion with Al(2)O(3) improved the shear bond strength between metal and ceramics used.
Keywords: Shear bond strength; metal-ceramic system; surface treatment